2013
DOI: 10.1007/s12640-013-9445-9
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury Induced by Perinatal Exposure to Glutaric Acid

Abstract: Glutaric acid (GA) is a neurotoxic metabolite that accumulates in the CNS of patients with glutaric acidemia-I (GA-I), a neurometabolic disease caused by deficient activity of glutaryl-CoA dehydrogenase. Most GA-I patients display characteristic CNS lesions, mainly in the gray and white matter of basal ganglia and cerebral cortex. Neurons and astrocytes are believed to be vulnerable to millimolar concentrations of GA. However, little is known about the effects of GA on oligodendrocytes (OL) and the myelination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Rat pups were injected at postnatal day 0 with PBS or GA into the cisterna magna to experimentally reproduce a GA-I like encephalopatic crisis as previously reported [23,24,26]. Then, animals were perfused with 1% EB in 4% PFA at 14 or 30 DPI to analyze EB extravasation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rat pups were injected at postnatal day 0 with PBS or GA into the cisterna magna to experimentally reproduce a GA-I like encephalopatic crisis as previously reported [23,24,26]. Then, animals were perfused with 1% EB in 4% PFA at 14 or 30 DPI to analyze EB extravasation.…”
Section: Resultsmentioning
confidence: 99%
“…Then, each animal was injected into the c isterna magna with either GA (1 μmol/g body weight, pH 7.4) [3-5], or an equal volume of vehicle (phosphate buffered saline (PBS), 10 mM, pH 7.4). A maximal volume of 5 μl was injected using a 30G needle attached to a Tygon tube extension to allow correct manipulation and zone identification [23,24,26]. The amount of GA administered ensured immediate high brain concentrations (~100 mM in the cerebrospinal fluid); which is hard to obtain by systemic injection due to limited flux across the BBB [27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the primary neuron model cannot substitute for model of cellular interaction participating in neurotoxicity (e.g., neuron, glial, vascular endothelial cells, etc.) [29]. Some studies suggested astrocyte proliferation protects neurons from the excitotoxic damage induced by 3-OHGA [30].…”
Section: Discussionmentioning
confidence: 99%